1977
DOI: 10.2307/1935118
|View full text |Cite
|
Sign up to set email alerts
|

Time and the Number of Herbivore Species: The Pests of Sugarcane

Abstract: Previous analyses have established that host species range in the most important determinant of plant— and animal—associated parasite species richness, and that the age of a host species within a region is, at most, much less important in determining this richness. However, these previous analyses were not able to completely rule out age as a cause, because the available host age estimations were crude and few host groups were available for comparison. This paper examines the arthropod pests of sugarcane (Sacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
131
3
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 25 publications
5
131
3
2
Order By: Relevance
“…A plant species introduced to a new habitat can be colonized rapidly by herbivores that recognize it as potential food and have the physiological capability to detoxify its secondary constituents (Strong 1974;Strong et al 1977;Singer et al 1993). Herbivores of native plants often shift onto novel hosts that are phytochemically similar to, but not necessarily related to, their traditional hosts (Strong et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…A plant species introduced to a new habitat can be colonized rapidly by herbivores that recognize it as potential food and have the physiological capability to detoxify its secondary constituents (Strong 1974;Strong et al 1977;Singer et al 1993). Herbivores of native plants often shift onto novel hosts that are phytochemically similar to, but not necessarily related to, their traditional hosts (Strong et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Strong and co-workers (Strong, 1974a, b , c;Strong & Levin, 1975Strong et al, 1977) interpret the 'rapid asymptotic' accumulation of herbivores onto introduced plants t o imply that biogeographic speciesrichness patterns of phytophagous insects are determined largely independently of time, after an initial period for colonization (up t o 300 years). Our results are consistent with this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A release from enemy attack may benefit invasive plants relative to native plants both through phenotypic responses to benign conditions (Mack et al 2000;Maron & Vila 2001;Keane & Crawley 2002) and by evolutionary shifts in allocation from defence to growth and reproduction (Blossey & Nö tzold 1995;Bossdorf et al 2005). Yet, studies of crop plants and introduced trees have shown that they have a diversity of insect herbivores comparable to native species within 350 years of their introduction (Strong 1974a,b;Strong et al 1977;Leather 1986;Andow & Imura 1994). Together these findings suggest a complex interaction of native herbivores and introduced plants in which low levels of herbivory at first may promote invasion success but then accumulation of herbivores over a period of centuries eventually equalizes invasive and native plant performance (defined here as naturalization).…”
Section: Introductionmentioning
confidence: 99%